If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 48) = x Reorder the terms: (48 + 2x) = x Remove parenthesis around (48 + 2x) 48 + 2x = x Solving 48 + 2x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 48 + 2x + -1x = x + -1x Combine like terms: 2x + -1x = 1x 48 + 1x = x + -1x Combine like terms: x + -1x = 0 48 + 1x = 0 Add '-48' to each side of the equation. 48 + -48 + 1x = 0 + -48 Combine like terms: 48 + -48 = 0 0 + 1x = 0 + -48 1x = 0 + -48 Combine like terms: 0 + -48 = -48 1x = -48 Divide each side by '1'. x = -48 Simplifying x = -48
| 7x-5-(6-8x)+2=3x-17+224 | | q-13=9 | | -5(t-6)-(t+1)=9 | | f(-2)=-3x+5 | | 5x^2+20x+15=y | | 17u-16u=13 | | 4a-3a=5 | | -4(t+4)=20 | | (4a-8)+(3a+14)=(5a-1) | | 5-2(x+8)=6x+5 | | (3a+14)=(5a-1)+(4a-8) | | 12+11= | | r^3-5r^2-25r+125=0 | | 25-11=2(x-6) | | (1-y)(3y+4)=0 | | (x+40)=x | | 7y-5=3y+7 | | 3x+35=17 | | 6-4w=2x+2 | | 45-4x=700 | | -c+4=13+4c-1 | | 6x-40=-22 | | 24+3x=196 | | -5(t+6)-(t+1)=9 | | 5y-8y=-14-19 | | (7x-10)=(5x+30) | | 18w=-36 | | 12-2x=48 | | (x+7)x=50 | | x=6x+9 | | 2(x-4)=5(x+7) | | 3y-5y-12=7y-88-5 |